Lobeglitazone Attenuates Airway Inflammation and Mucus Hypersecretion in a Murine Model of Ovalbumin-Induced Asthma - Shin, Na-Rae; Park, Sung-Hyeuk; Ko, Je-Won; Cho, Young-Kwon; Lee, In-Chul; Kim, Jong-Choon; Shin, In-Sik; Kim, Joong-Sun (Frontiers in Pharmacology, 2018)
Lobeglitazone (LB) is a novel agonist of peroxisome proliferator-activated receptor (PPAR)-α and γ that was developed as a drug to treat diabetes mellitus. We explored the ameliorative effects of LB on allergic asthma using a murine model of ovalbumin (OVA)-induced asthma. To boost the immune response of animals, OVA sensitization was performed on days 0 and 14. LB (250 or 500 µg/kg) was administered by oral gavage on days 18 to 23, and the OVA challenge was performed using an ultrasonic nebulizer on days 21 to 23. Plethysmography showed airway hyperresponsiveness (AHR) on day 24. LB treatment effectively decreased inflammatory cell recruitment, T-helper type 2 cytokines in the bronchoalveolar lavage fluid, and immunoglobulin (Ig) E in the serum of the animals with OVA-induced asthma, which was accompanied by a marked reduction in AHR. It also decreased airway inflammation, mucus hypersecretion, phosphorylation of nuclear transcription factor-kappa-B (NF-κB), and expression of activating protein (AP)-1 and mucin 5AC (MUC5AC). Overall, LB effectively attenuated the pathophysiological changes of asthma and its effects appear related to a reduction in the phosphorylation of NF-κB and the expression of AP-1. Thus, our results suggest that LB has a potential to treat allergic asthma.